2011
DOI: 10.1590/s0074-02762011000400015
|View full text |Cite
|
Sign up to set email alerts
|

The in vitro leishmanicidal activity of hexadecylphosphocholine (miltefosine) against four medically relevant Leishmania species of Brazil

Abstract: The in vitro leishmanicidal activity of miltefosine® (Zentaris GmbH) was assessed against four medically relevant Leishmania species of Brazil: Leishmania (Leishmania) amazonensis, Leishmania (Viannia) braziliensis, Leishmania (Viannia) guyanensis and Leishmania (Leishmania) chagasi. The activity of miltefosine against these New World species was compared to its activity against the Old World strain, Leishmania (Leishmania) donovani, which is known to be sensitive to the effects of miltefosine. The IC50 and IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 16 publications
5
26
0
Order By: Relevance
“…In our hands, the CC 50 values obtained for THP-1 and HMØ were 6-to 12-fold lower than those with HePC, which showed cytotoxic levels similar to those described earlier by others (26,43). Compound 1 had the most interesting SI, which was 4-fold higher than that of HePC.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In our hands, the CC 50 values obtained for THP-1 and HMØ were 6-to 12-fold lower than those with HePC, which showed cytotoxic levels similar to those described earlier by others (26,43). Compound 1 had the most interesting SI, which was 4-fold higher than that of HePC.…”
Section: Discussionsupporting
confidence: 86%
“…Both of them had no biological effect, implying that the activity is conferred by the furanoside ring. Our IC 50 results using HePC on promastigotes are in coherence with previously published data (26,42), thus allowing reliable comparison of efficacy between our molecules and a reference treatment.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Due to this, a different sensitivity of theses parasites to the tested extracts was expected. Previous in vitro studies have also shown differences in sensitivity of Leishmania species to different reference drugs, including pentavalent antimonials, amphotericin B (Minodier and Parola 2007), miltefosine (De Morais-Teixeira et al 2011) and crude or purified plant extracts (Braga et al 2007, Fabri et al 2012a. Among the 17 methanolic extracts tested, 11 showed leishmanicidal activity against at least one promastigote forms of Leishmania species with IC 50 values ranging from 5.0 to 88.3 µg/mL.…”
Section: Resultsmentioning
confidence: 94%
“…Miltefosine, a hexadecylphosphocholine, was initially studied as an anti-tumour agent [5]; more recently, it was described to exhibit both in vitro and in vivo activity against Leishmania parasites [6][7][8][9][10][11]. Oral administration of miltefosine has been used in India to treat visceral leishmaniasis (VL) since 1998.…”
Section: Introductionmentioning
confidence: 99%